Bulgaria : Financial Sector Assessment Program: Technical Note. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note evaluates the financial safety net and crisis management for Bulgaria. Since the 2008 IMF Financial Sector Assessment Program Update, Bulgaria's financial safety net and crisis management arrangements, including bank resolution and contingency planning, have improved. In 2015, to implement pertinent European Union rules, Bulgaria introduced a resolution regime for banks and investment firms; designated resolution authorities for said financial institutions; and established mechanisms to fund resolution measures. Despite the improvements, the financial safety net and crisis management arrangements face crucial challenges because none of their components is fully developed. To ensure operational capacity to rapidly deploy recovery and resolution tools, further actions are needed to strengthen the safety net and crisis management arrangements.